POCER1914: Elucidation of Gallic Acid Degradation Pathway from Labisia Pumila via Mass Spectroscopy Technique - Afiqah, Yeop; Pang, Sook Fun; M. M., Yusoff; Sureena, Abdullah; Jolius, Gimbun (University of Nottingham, 2019)
Thermal degradation kinetics and mechanism of gallic acid was investigated at temperatures ranging from 60 to 120 °C with a heating time of 90 min. The ultra-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometer was used to elucidate the degradation mechanism of gallic acid in the heated sample. The degradation kinetics of gallic acid shows a good fit with the 1st order model with correlation coefficients of R2 ≥ 0.96. The kinetics rate constant (k) were 0.0011, 0.0038 and 0.0076 min-1 at the temperature of 60, 90 and 120 °C, respectively. This finding in this work may serve as a useful guide to minimize the gallic acid degradation and formation of unwanted by-products during processing of L. pumila.